(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
The article discusses Genghis Khan’s invasion of Central Asia, the overthrow of the Khorezm Shahs, and the fact that Genghis Khan’s descendants embraced Islam and even became Sufis. Quotations from the book «History of Four Nations» by Mirzo Ulugbek clarify this small study